THE INFLUENCE OF ISLAMIC MOTIVATION AND WORK SATISFACTION ON EMPLOYEE PERFORMANCE CASE STUDY OF NATIONAL AMIL ZAKAT INSTITUTION OF BAITUL MAAL HIDAYATULLAH SURABAYA - Nur Shofa Barkhiyyah; Ari Prasetyo (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
This study aims to analyze the influence partially and simultaneously whether the motivation variables of Islam and job satisfaction have a significant effect on Islamic work performance at the Baitul Maal Hidayatullah National Amil Zakat Institution in Surabaya. The research method used in this study is a quantitative approach. The process of data collection used was a questionnaire, with a saturated sampling technique with the criteria of all employees of the Baitul Maal Hidayatullah National Amil Zakat Institution Surabaya numbering 37 respondents. The analysis technique used in this study is the multiple linear regression. This study indicated that the motivation variable has a significant negative influence. It shows that motivation does not influence employee work performance. On the other hand, the second variable, the work satisfaction variable, has a significant positive. It means that work satisfaction influences employee work performance.Keywords: Islamic Work Motivation, Satisfaction, and Employee Work PerformanceREFFERENCE Arep, Ishak dan Hendri, Tanjung. (2013). Manajemen motivasi. Jakarta: PT. Gramedia Widiasarana Indonesia.Alex S. Nitisemito. (2004). Manajemen personalia. Jakarta: Ghalia Indonesia.Budiyanto, M.T, Eko. (2013). Sistem informasi manajemen sumber daya manusia. Yogyakarta: Graha Ilmu.Erlina, Eni. (2018). Peran organizational citizenship behavior sebagai pemediasi pengaruh kepuasan kerja terhadap kinerja perawat. Skripsi tidak diterbitkan. Malang: Fakultas Ekonomi UIN Maulana Malik Ibrahim Malang. Ghozali, Imam. (2013). Aplikasi analisis multivariate dengan program SPSS. Semarang: Badan Penerbit Universitas DoponegoroHasibuan, Malayu. (2010). Manajemen sumber daya manusia. Jakarta: PT Bumi Aksara.Indrasari, Meithiana. (2017). Kepuasan kerja dan kinerja karyawan. Yogyakarta: Indomedia Pusaka.Jusmaliani. (2011). Pengeloalaan sumber daya insani. Jakarta: Bumi Aksara.Kuswadi. (2004). Cara mengukur kepuasan karyawan. Jakarta: Komputindo.Mangkunegara, Anwar. (2005). Evaluasi kinerja sumber daya manusia. Bandung: Refika Aditama Panggabean, M. S. (2004). Manajemen sumber daya manusia. Jakarta: Ghalia Indonesia. Riniwati, Harsuko. (2011). Mendongkrak motivasi dan kinerja: pendekatan pemberdayaan SDM. Malang: UB PressRobbins, Stephen P. & Judge, Timothy A. (2008). Perilaku organisasi, buku 1, cetakan 12. Jakarta: Salemba Empat.Tasmara, Toto. (2002). Membudayakan etos kerja Islami. Jakarta: Gema Insani.Saleh, A. M. (2009). Bekerja dengan hati nurani. Jakarta: Penerbit Erlangga.Sedarmayanti. (2009). Sumber daya manusia dan produktivitas kerja. Bandung: Mandar Maju.----------. (2011).  Manajemen sumber daya manusia. Bandung: PT. Refika Aditama. Setiawan dan Kusrini, D. E., dan. (2010). Ekonometrika. Yogyakarta: Andi.Siagian, S.P. (2004). Manajemen sumber daya manusia. Jakarta: PT Bumi Aksara.----------. (2012). Teori motivasi dan aplikasinya. Jakarta: Rineka Cipta.Simamora. (2004). Manajemen Sumber Daya Manusia. Edisi Ke-3. Yogyakarta: STIE YKPN.Siregar, S. (2015). Metode penelitian kuantitatif dilengkapi dengan perbandingan perhitungan manual & SPSS. Jakarta: Prenada Media.Sugiyono. (2015). Metode penelitian bisnis (pendekatan kuantitatif, kualitatif, dan R&D). Bandung: Alfabeta.----------. (2011). Metode penelitian bisnis (pendekatan kuantitatif, kualitatif, dan R&D). Bandung: Alfabeta.Sugiyono, & Susanto, A. (2015). Cara mudah belajar SPSS & Lisrel (teori dan aplikasi untuk analisis data penelitian). Bandung: CV Alfabeta.Wahab, R.B. (2012). Pengaruh kepuasan kerja dan motivasi kerja terhadap kinerja karyawan PT. Bank Mandiri. Skripsi tidak diterbitkan. Makassar: Fakultas Ekonomi dan Bisnis Universitas Hasanuddin.Yummi, Auffah. (2016). Kemaslahatan dalam Konsep Maqashid Al-Syariah. Jurnal Tarbiyah, 6(2), 47-57. http://dx.doi.org/10.30821/niz.v6i2.70Zainal, Veithzal Rivai, dkk. (2018). Penilaian kinerja sumber daya insani untuk perusahaan. Yogyakarta: BPFEZainal, Veithzal Rivai & Sagala, E.J. (2009).  Manajemen sumber daya manusia untuk perusahaan. Jakarta: Rajagrafindo Persada.